2022
DOI: 10.1039/d1cp05797a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the carbonate effect on water oxidation over metal oxide photocatalysts/photoanodes

Abstract: Photocatalytic/photoelectrochemical water splitting using metal oxide semiconductors is a promising technology for direct and simple solar-energy conversion. The addition of carbonate salts to an aqueous reaction solution has been known...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The Pople‐type split valence basis set of 6‐311+G(d,p) [23] was used for H, O, and S atoms, [24] whereas the Stuttgart/Dresden effective core potential basis set (SDD) was used for Sn and W atoms [25,26] . This approach provided appropriate geometries for isolated molecules that consisted of H, O, and S atoms (Figure S1), as well as W−O and Sn−O structures, [27,28] as reported previously [17,29–31] . Frequency calculations were performed to confirm optimized structures with no imaginary frequencies, which corresponded to the real minima on the entire potential energy surface.…”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pople‐type split valence basis set of 6‐311+G(d,p) [23] was used for H, O, and S atoms, [24] whereas the Stuttgart/Dresden effective core potential basis set (SDD) was used for Sn and W atoms [25,26] . This approach provided appropriate geometries for isolated molecules that consisted of H, O, and S atoms (Figure S1), as well as W−O and Sn−O structures, [27,28] as reported previously [17,29–31] . Frequency calculations were performed to confirm optimized structures with no imaginary frequencies, which corresponded to the real minima on the entire potential energy surface.…”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…[25,26] This approach provided appropriate geometries for isolated molecules that consisted of H, O, and S atoms (Figure S1), as well as WÀ O and SnÀ O structures, [27,28] as reported previously. [17,[29][30][31] Frequency calculations were performed to confirm optimized structures with no imaginary frequencies, which corresponded to the real minima on the entire potential energy surface. They were also conducted to determine zero-point vibrational energies.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we calculated the H 2 CO 3 oxidation mechanism proposed by Kusama et al (Supplementary Fig. 8 ) on the LaAlO 3 surface 51 . Our results agree well with the report by them and show that the first proton removal from the adsorbed H 2 CO 3 is the rate-limiting step.…”
Section: Resultsmentioning
confidence: 99%
“…The large dimensions of the photoelectrode (2 Â 3 cm 2 ) prevented the removal of Cl 2 gas from the surface, consequently promoting photolysis and Density functional theory (DFT) calculations were performed to scrutinize the kinetic aspects governing the selectivity for O 2 /HClO production. [24][25][26][27][28][29][30] Using a commonly accepted theoretical description involving four proton-coupled electron-transfer (PCET) steps with two H 2 O molecules, [31][32][33][34][35][36] the mechanisms underlying intermediate formation and oxidation of HCl and H 2 O were investigated using the Ti(OH) 2 -O 2 -Ti(OH) 2 cluster model for rutile TiO 2 . 34,35,37 The DFT results indicated that the first deprotonation step from the adsorbed HCl or H 2 O was the rate-limiting step for both reactions, similar to those reported previously for H 2 O oxidation (Fig.…”
mentioning
confidence: 99%